Forensic Science has a significant role in the criminal justice system: Exploring the Role of Forensic Science in the Criminal Justice System (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In recent times, the use of technology in criminal investigations has been a main achievementin criminal justice advancement. The courts, on the other hand, consider these tangible evidences, whichare otherwise unfailing, and evaluate the offender's innocence or guilt with greater precision. The use oftechnology in criminal investigations has grown inextricably linked to the criminal justice system'sefficiency and efficacy.It is a branch of technology that acts inside the constraints of the legal system. Itstask is to offer assistance to individuals engaging in investigations as well as accurate statistics tocourts to be used in the decision of criminal and civil disputes.Our study’s purpose is to examine thecriminal framework that governs the software of Forensic .Science. Furthermore, despite majortechnological improvements in recent decades, the Function of forensic technological know-how inIndian criminal justice has remain. or limited, as will be investigated in this study. The goal of forensicinvestigation and trial should be to provide outcomes, so that victims of heinous atrocities obtainspeedy redress and justice.